Impacto da inclusão de extrato tanífero de Acacia mearsnsii na dieta sobre o metabolismo energético em bovinos - Ávila, Suélen Capa de (2016)
The objective of the study is to evaluate the effect of Acacia mearnsii tannin extract on balance of nutrients and efficiency of energy of steers. The experiment was conducted in a Latin Square design, with eight Holstein steers (338 ± 32,2 kg body weight (BW)). The animals have been housed in metabolism cages, fed on a diet composed by 90% corn silage and 10% concentrate at two levels of intake with or without the inclusion of Acacia mearnsii tannin extract. The treatment structure was a 2 × 2 factorial; intake, 1.2 versus 1.8 × NEm and tannin addition vs. control. The experiment was conducted in four periods of 21 days, of which the first 14 days were intended for the adaptation of the animals to the diets and the last 7 days to evaluate whole body energy balance and endogenous heat production. For measurement of heat production and nutrient balance, expired respiratory gases, urine, and feces were collected. Fecal and urine collections were taken during 7 days. Whole-body heat production (HP) was calculated by indirect calorimetry from O2 consumption and CO2 production and corrected for CH4 production and urinary N excretion using the equation proposed by Brouwer (1965). The inclusion of tannin extract had no effect on energy and nitrogen balance. The two levels of intake had effect on energy retention and whole-body heat production (P<0.001).